Intraindustry differences in conduct and performance : viable strategies in U.S. manufacturing industries - Caves, Richard E.; Pugel, Thomas A. ([New York] : New York University, Graduate School of Business Administration, Salomon Brothers Center for the Study of Financial Institutions, 1980)
This study develops a consistent posture toward intraindustry differences in firm behavior . The study is an attempt to explore differences in behavior and performance among firms in 73 individual U.S. manufacturing industries.
Bibliography: p. 49-50.
osc 30/01/2019
Loans
Keywords: Industries; Industries; Manufacturing industries; Industrial productivity